Missing persons - Brandman, Michael (Poisoned Pen Press, 2020)
"When LAPD homicide detective Buddy Steel, called home by his ailing sheriff father to take over as deputy, begins investigating the possible disappearance of a famous local televangelist's wife no one, from family members to ministry security and staff to the prosecutor's office seems inclined to help Buddy in his investigation. But the more he pokes and prods, the more he realizes that the Bible-thumping family and their television empire may be an elaborate cover for a less-than--holy enterprise. Will Buddy pay the ultimate price for refusing to look the other way?"--